(untitled) (Acta Scientiarum. Biological Sciences, 2012)
This work carried out to evaluates the polymorhism in the silkworm of different lineages using the isoenzymes electrophoresis to detect biochemical markers and to investigate the genetics of populations for those lineages. They were used as samples individual extracts of silk glands of second day old larvas of the fifth instar, originating from seven Japanese lineages and eight pure Chinese lineages maintained by the Cocamar-Cooperativa Agroindustrial de Maringá. The isozymes acid phosphatase (ACP), alkaline phosphatase (AKP) and carbonic anhydrase (CA) they were submitted to the electrophoresis in starch gels 14%. The esterases (EST) were analyzed in polyacrylamide gels to 10% and stained with Î± and b-naphtyl acetate. The total of 21 loci was detected, and 04 (19.05%) they are polymorphic, Est-11, Acp, Akp, Ca. The fixation index (Fis) for the analyzed isozymes it was 0.0751, indicating excess of homozygotes. The value of Fst (0.6128) it shows that the lineages are well differentiated. The dendrogram obtained with the values of genetic distance didn’t separate the Chinese and Japanese lineages analyzed totally. That preliminary evaluation of the lineages of B. mori shows that they present genetic material that it can be used in breeding programs that have the purpose of producing hybrid for silk production.